Pelatihan Desain Mahar Eco-Friendly: Kreasi Mahar Berbahan Daur Ulang - Aini, Yuni Nur; Ulya, Zahrotul; Yunani, Zerli Feni; Chofifah, Zulfa Yuliana; Fikriyah, Ashfa (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Eco-friendly dowry design training aims to increase people's knowledge and skills in processing waste into economically valuable products. This activity was carried out by the community service team with the Ardian Collection MSME, Tamanan Village, Bandar Kidul District, Kediri City, as an effort to manage household waste, especially used paper and plastic, through the 3R process (reduce, reuse, recycle). This training provides an understanding of systematic and sustainable waste management, as well as utilizing used items such as plastic bottles, cloth and newspapers into dowry works of art. Training methods include outreach, demonstrations and direct practice in creating waste-based products. As a result, participants succeeded in producing dowry works made from recycled materials that were aesthetic and of high selling value, while reducing environmental waste. This activity is expected to improve community welfare through optimizing waste into value-added goods and supporting environmental conservation efforts.